The signalling mucin Msb2 regulates surface sensing and host penetration via BMP1 MAP kinase signalling in Botrytis cinerea. (27th February 2015) - Leroch, Michaela; Mueller, Nathalie; Hinsenkamp, Isabel; Hahn, Matthias
Summary Botrytis cinerea is a necrotrophic fungus that infects a wide range of fruit, vegetable and flower crops. Penetration of the host cuticle occurs via infection structures that are formed in response to appropriate plant surface signals. The differentiation of these structures requires a highly conserved mitogen‐activated protein (MAP) kinase cascade including the MAP kinase BMP1. In yeast and several plant‐pathogenic fungi, the signalling mucin Msb2 has been shown to be involved in surface recognition and MAP kinase activation. In this study, a B. cinerea msb2 mutant was generated and characterized. The mutant showed normal growth, sporulation, sclerotia formation and stress resistance. In the absence of nutrients, abnormal germination with multiple germ tubes was observed. In the presence of sugars, normal germination occurred, but msb2 germlings were almost unable to form appressoria or infection cushions on hard surfaces. Nevertheless, the msb2 mutant showed only a moderate delay in lesion formation on different host plants, and formed expanding lesions similar to the wild‐type. Although the wild‐type showed increasing BMP1 phosphorylation during the first hours of germination on hard surfaces, the phosphorylation levels in the msb2 mutant were strongly reduced. Several genes encoding secreted proteins were found to be co‐regulated by BMP1 and Msb2 during germination. Taken together, B. cinerea Msb2 is likely to represent a hard surface sensor of germlings and hyphae that triggers infection structure formation via the activation of the BMP1 MAP kinase pathway.